The antagonistic Metschnikowia andauensis produces extracellular enzymes and pulcherrimin, whose production can be promoted by the culture factors - Enikő Horváth (Nature Portfolio, 2021)
Abstract Biological control against microbial infections has a great potential as an alternative approach instead of fungicidal chemicals, which can cause environmental pollution. The pigment producer Metschnikowia andauensis belongs to the antagonistic yeasts, but details of the mechanism by which it inhibits growth of other microbes are less known. Our results confirmed its antagonistic capacity on other yeast species isolated from fruits or flowers and demonstrated that the antagonistic capacity was well correlated with the size of the red pigmented zone. We have isolated and characterized its red pigment, which proved to be the iron chelating pulcherrimin. Its production was possible even in the presence of 0.05 mg/ml copper sulphate, which is widely used in organic vineyards because of its antimicrobial properties. Production and localisation of the pulcherrimin strongly depended on composition of the media and other culture factors. Glucose, galactose, disaccharides and the presence of pectin or certain amino acids clearly promoted pigment production. Higher temperatures and iron concentration decreased the diameter of red pigmented zones. The effect of pH on pigment production varied depending of whether it was tested in liquid or solid media. In addition, our results suggest that other mechanisms besides the iron depletion of the culture media may contribute to the antagonistic capacity of M. andauensis.